Biofabrication: 'Printability' of Candidate Biomaterials for Extrusion Based 3D Printing: State‐of‐the‐Art (Adv. Healthcare Mater. 16/2017). Issue 16 (23rd August 2017) - Kyle, Stuart; Jessop, Zita M.; Al‐Sabah, Ayesha; Whitaker, Iain S.
Abstract : 3D bioprinting has the potential to replicate complex tissue architecture and biomanufacture physiologically relevant multicellular constructs on demand. In article number1700264, Stuart Kyle, Iain S. Whitaker, and co‐workers review a new generation of bioinks with suitable biocompatibility and high shape/print fidelity, that have the potential to match or exceed the physical, chemical and biological properties of human tissue, when combined with the appropriate cell source. Image of 3D Bioprinter kindly provided by Aether.